Desain Mixer-Settler Pada Prarancangan Pabrik Acrylonitrile Butadiene Styrene (ABS) Dengan Proses Emulsi - Revika Wulandari; Sri Helianty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Acrylonitrile Butadiene Styrene (ABS) is a thermoplastic polymer. Lightness, rigidity, impact resistance, ease of processing, resistance to chemicals and applicable are ABS properties interesting. The base ABS is added methyl methacrylate to enhance the appearance and become a transparent material. The ABS consumption in 2018-2026 tends to increase due to its properties, especially in the lightweight engineering plastics region. Our final project is proposed to design a new ABS plant that meets 10% of domestic ABS needs. This project decreases the country's foreign exchange, and allocates jobs for local labour. Also, ABS domestic strengthens the upstream industries, such as a vehicle and textile. The ABS plant construction is going to hold for three years in 2022-2025, in the Tanjung Buton Industrial Estate. The ABS plant has 115,000 tons/year capacity for emulsion processing, per the average ABS capacity in Asia of 120,000 tons/year. This capacity is to meet domestic needs and the Asia market. The ABS Emulsion Process consists of 3 stages Polybutadiene Synthesis, the grafting polymerization reaction stage and the product separation stage. The main design is the mixer-settler used to separate the remaining CaCl2 which is still present in the ABS. Technically, the separation process using a mixer-settler consists of 2 stages, namely the extraction stage occurring in the stirred tank and the separation stage occurring in the settler. The mixer-settler equipment was purchased from the Haohua Zhongyi Hebei Advanced composite Co., Ltd manufacturer with a volume used of 133 m3, a tank diameter of 18 ft, a total tank height of 24 ft and a rectangular settler used as a settler. The types of heads used are torispherical flanged and dished heads. The material used is Fiberglass Reinforced Plastics ASTM D3299. The resulting ABS product is transparent in the form of pellets as intermediate goods. The pre-designed economic analysis of this factory obtained a Return On Investment (ROI) of 33.17%, a payback period (PBP) of 1.67 years, a BEP of 32% and an IRR of 22.74%. The feasibility analysis shows that the ABS plant project is feasible. With the increasing industrial development in Indonesia, it is estimated that the demand for ABS raw materials in the coming years will also increase. Keywords : emulsi, mixer-settler, polymer, thermoplastic